Analisis Upaya Guru dalam Mengatasi Kesulitan Membaca Siswa Kelas II Di Masa Pandemi Covid-19 SDN 305 Inpres Sa’tandung Kecamatan Saluputti Kabupaten Tana Toraja - Theresyam Kabanga'; Melsi Melsi (LPPM UKI Toraja, 2021)
The purpose of this study is to describe the teacher's efforts in overcoming reading difficulties for grade II students during the COVID-19 pandemic at SDN 305 Inpres Sa'tandung. This study describes the teacher's efforts in overcoming reading difficulties and the difficulties faced by students when reading. This type of research is a qualitative research with a descriptive design. This study focused on analyzing the teacher's efforts in overcoming reading difficulties. Data obtained by: observation, interviews and documentation. After this research was carried out, it was found that there were some children who still had difficulty in reading especially during this covid-19 pandemic, in this case it was influenced by limited learning at school so that when students returned home students became lazy to read, teachers at school tried to find solutions to overcome the problems of students who have difficulty reading by always accompanying students while studying and outside of learning according to the difficulties of the students, paying special attention, creating an atmosphere in the classroom to create a pleasant learning atmosphere. From the results of this study, it can be concluded that the teacher has tried to overcome the reading difficulties of grade II students during the COVID-19 pandemic at SDN 305 Inpres Sa'tandung, Saluputti sub-district, Tana Toraja district by fostering students who have reading difficulties.